The Influence of Internal Communication on The Performance of Banten Province Public Works and Spatial Planning Service Employees in the Educational - Nurmala, Lala; Haiah, Fithri; Juariah, Siti; Maliki, Budi Ilham (Cendekia: Jurnal Pendidikan dan Pembelajaran, 2023)
Human resources have an important role both individually and in groups because they are the main driving force for the smooth running of activities, even the back and forth of the organization is determined by the existence of human resources. Every agency will always try to improve the performance of its employees, with the hope that organizational goals will be achieved. The population in this study were all employees at the Department of Public Works and Spatial Planning (DPUPR) of Banten Province, totaling 200 employees. While the sample is part of the population, the sample taken in this study used 42 samples (PNS). The purpose of this study was to determine the effect of internal communication on employee performance through work stress at the Department of Public Works and Spatial Planning (DPUPR) of Banten Province.The results of this study indicate that: Internal communication has a positive and significant effect on employee performance, and work stress has no significant effect on employee performance at the Department of Public Works and Spatial Planning (DPUPR) Banten Province.